Examinations of effects of socio-demographic features and disease-related data of patients with hemodialysis on the quality of life - Elif Togay; Hatice Öntürk Akyüz (Scientific Reports)
Abstract This study aimed to detect the effects of demographic features and disease-related data of individuals with hemodialysis treatment on quality of life. The research universe consisted of 113 patients who received dialysis treatment in three state hospitals. Sampling was not used in this research with 97 volunteer patients who complied with the study criteria. The data collection process was performed face-to-face between 15 March and 15 April 2021. Data was collected using the Participant Information Form and the Quality of Life Scale (Short From-36). In our research, 50.5% of participants were male and 49.5% were female. The age of 61.9% of participants was ≥ 51 years and 78.4% were married. Most participants (67%) had ≥ 3 children, 35.1% received dialysis treatment for 3–10 years, 90.7% had dialysis three times a week, and 64.9% had an arterio-venous fistula vascular access line. In addition, 24% had another family member who received dialysis treatment, with hypertension as the etiology in 35.6% of chronic renal failure (CRF). The findings showed that 93.8% patients had no previous transplantation, and 62.9% considered future transplantation.Within the scope of this research, the findings suggest that the quality of life of dialysis patients was poor. Demographic features and disease data affected the quality of life at different levels.